The Effect Of Tax Socialization, Tax Knowledge And Tax Morale On Tax Compliance - Rahmawati, Sari (International Journal of Educational Research & Social Sciences, 2022)
This research is intended to gain insight of the partial and simultaneous influence of tax socialization, tax knowledge, and tax morale to tax compliance on taxpayer in KPP Pratama, Bandung. This research as a method of causal explanatory, with linear regression analysis. This research is using questionnaire as an instrument, that developed according to the theoretical framework, and was considered valid and reliable enough. The population was the small and middle enterprises in Bandung, on the 2016 year.The sampling used was probabilistic sampling, using simple random sampling methods.The researcher was using the data from 100 taxpayer randomly assigned from all Bandung KPP Offices.According to the result of the study, it is found that there is a significant effect of tax socialization, tax knowledge, and tax morale. Thus, the researcher advises to the KPP and Tax Directorate, as the governmental body that manages the tax.The organization is advised to routinely uses tax socialization, tax knowledge, and doing routine training to increase the tax morale, as an effort to increase the taxpayer’s compliance.